Cultures of communication theologies of media in early modern Europe and beyond - Puff, Helmut 1961-; Strasser, Ulrike 1964-; Wild, Christopher J. 1967- (University of Toronto Press, 2017)
"Contrary to the historiographical commonplace "no Reformation without print" Cultures of Communication examines media in the early modern world through the lens of the period's religious history. Looking beyond the emergence of print, this collection of ground-breaking essays highlights the pivotal role of theology in the formation of the early modern cultures of communication. The authors assembled here urge us to understand the Reformation as a response to the perceived crisis of religious communication in late medieval Europe. In addition, they explore the novel demands placed on European media ecology by the acceleration and intensification of global interconnectedness in the early modern period. As the Christian evangelizing impulse began to propel growing numbers of Europeans outward to the Americas and Asia, theories and practices of religious communication had to be reformed to accommodate an array of new communicative constellations across distances, languages, cultures."
"This book grew out of conferences entitled "Theologies of Media, Cultures of Communication in Early Modern Europe and Beyond," held at the William Andrews Clark Memorial Library in 2009-10." (Seite [xi])
Keywords: Geschichte 1500-1600; Intercultural communication / Europe / History / 16th century; Communication / Religious aspects / Christianity; Mass media / Religious aspects / Christianity; Theology / Europe / History / 16th century; Reformation; Intercultural communication; Theology; Christentum; Geschichte; Interkulturelle Kommunikation; Massenmedien; Religion; Theologie; Kommunikation; Mission; Druckgrafik; Medialität; Europe; Europa; Konferenzschrift -- 2009-2010 -- Los Angeles, Calif.